2003
DOI: 10.1021/bi034290i
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake and Metabolism of DNA Frayed Wires

Abstract: DNA frayed wires are a novel, multistranded form of DNA that arises from interactions between single-stranded oligodeoxyribonucleotides with the general sequence d(N(x)G(y)) or d(G(y)N(x)), where y > 10 and x > 5. Frayed wires exhibit greater stability with respect to thermal and chemical denaturation than single- or double-stranded DNA molecules and, thus, may have potential usefulness for DNA drug delivery. However, the stability and uptake of frayed wires have not been investigated in biological systems. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…As we mentioned above, DNA FW consist of a mixture of species with different aggregation numbers, thus, the molecular weight of these supermolecular structures can be quite large. Despite this, we have shown in a previous study that in comparison to singlestranded DNA, DNA FW exhibit higher intracellular accumulation, increased nuclear localization, and diminished cytotoxicity in the human hepatoma cell line, HepG2 [19]. Given the characteristics of DNA FW , it seemed apparent that they might be potentially useful as an alternative DNA drug delivery system; however, further characterization is required.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…As we mentioned above, DNA FW consist of a mixture of species with different aggregation numbers, thus, the molecular weight of these supermolecular structures can be quite large. Despite this, we have shown in a previous study that in comparison to singlestranded DNA, DNA FW exhibit higher intracellular accumulation, increased nuclear localization, and diminished cytotoxicity in the human hepatoma cell line, HepG2 [19]. Given the characteristics of DNA FW , it seemed apparent that they might be potentially useful as an alternative DNA drug delivery system; however, further characterization is required.…”
Section: Introductionmentioning
confidence: 90%
“…The non-guanine bases branch off from the guanine-rich stem and behave in many respects like single-stranded DNA. Previous studies have shown that DNA FW possess greater chemical, enzymatic, and thermal stability than regular DNA molecules [19,30]. As we mentioned above, DNA FW consist of a mixture of species with different aggregation numbers, thus, the molecular weight of these supermolecular structures can be quite large.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations